Towards a deeper understanding of the purchase of souvenirs - Amaro, Suzanne (2019)
Although there are many studies addressing the purchase of souvenirs, a few provide practical insights for practitioners in the souvenir industry regarding tourist’s preferred souvenir attributes, what they purchase, and how much they spend. Furthermore, little is known about souvenir collectors’ preferences. To address these gaps, this study analyzes tourists’ souvenir purchasing behavior with both quantitative (277 responses to a questionnaire) and qualitative (85 interviews) methods. The results indicate that the quality of the souvenir, gift appropriateness, and having the name or design of the place visited were the souvenir attributes most valued by the tourists. The results also reveal the importance of souvenir collectors, since they buy more souvenirs and spend higher amounts per souvenir. Further insights are given regarding the purchase of souvenirs, providing practical implications for practitioners in the souvenir industry.